Determinan Minat Menabung Masyarakat di Bank Syariah: Studi Empiris di Kota Jambi - Titin Agustin Nengsih; Arsa Arsa; Pradita Sari Putri (STIE Perbanas Surabaya, 2021)
This research is motivated by the lack of public interest for saving at Islamic Banks which the results of preliminary observations are most people save at conventional banks. Location, trust, knowledge, promotion and service quality are thought to influence people's interest for saving at Islamic Banks. This study aims to determine the effect of location, trust, knowledge, promotion, and service quality on the interest of the people of Jambi City to save in Islamic banks. This study uses a quantitative approach and the data analysis method used is Multiple Linear Regression Analysis. The results of data analysis indicate that trust, promotion and service quality variables had a significant effect on people's interest in saving. Furthermore, the location and knowledge variables didn’t affect the interest in saving. Indeed, the analysis model also shows that location, trust, knowledge, promotion and service quality together have a significant effect on the interest in saving with the determinant coefficient value for this model of 47.8%.